Crystal Structures and Thermodynamic Analysis Reveal Distinct Mechanisms of CD28 Phosphopeptide Binding to the Src Homology 2 (SH2) Domains of Three Adaptor Proteins - Inaba, Satomi; Numoto, Nobutaka; Ogawa, Shuhei; Morii, Hisayuki; Ikura, Teikichi; Abe, Ryo; Ito, Nobutoshi; Oda, Masayuki (The Journal of biological chemistry, 2017)
Full activation of T cells and differentiation into effector T cells are essential for many immune responses and require co-stimulatory signaling via the CD28 receptor. Extracellular ligand binding to CD28 recruits protein-tyrosine kinases to its cytoplasmic tail, which contains a YMNM motif. Following phosphorylation of the tyrosine, the proteins growth factor receptor-bound protein 2 (Grb2), Grb2-related adaptor downstream of Shc (Gads), and p85 subunit of phosphoinositide 3-kinase may bind to pYMNM (where pY is phosphotyrosine) via their Src homology 2 (SH2) domains, leading to downstream signaling to distinct immune pathways. These three adaptor proteins bind to the same site on CD28 with variable affinity, and all are important for CD28-mediated co-stimulatory function. However, the mechanism of how these proteins recognize and compete for CD28 is unclear. To visualize their interactions with CD28, we have determined the crystal structures of Gads SH2 and two p85 SH2 domains in complex with a CD28-derived phosphopeptide. The high resolution structures obtained revealed that, whereas the CD28 phosphopeptide bound to Gads SH2 is in a bent conformation similar to that when bound to Grb2 SH2, it adopts a more extended conformation when bound to the N- and C-terminal SH2 domains of p85. These differences observed in the peptide-protein interactions correlated well with the affinity and other thermodynamic parameters for each interaction determined by isothermal titration calorimetry. The detailed insight into these interactions reported here may inform the development of compounds that specifically inhibit the association of CD28 with these adaptor proteins to suppress excessive T cell responses, such as in allergies and autoimmune diseases.